Families Affected by Parental Cancer: Quality of Life, Impact on Children and Psychosocial Care Needs - Inhestern, Laura; Johannsen, Lene Marie; Bergelt, Corinna (Frontiers in Psychiatry, 2021)
Parental cancer poses major challenges for families with minor children. Due to diagnosis and treatment family life is disrupted. To prevent long-term consequences in all family members and to design needs-oriented family-centered interventions, further understanding of the family’s situation including the impact on the children, quality of life levels and the parental psychosocial needs is necessary. This study aims at investigating the impact of parental cancer on the minor children, family-specific psychosocial needs and quality of life levels of parents and children. Cancer patients parenting at least 1 minor child (< 18 years) were eligible for study participation. In total, n=86 cancer patients under treatment participated in the study. After excluding participants without a minor child, 78 patients remained for analyses. We assessed children’s quality of life using the parent proxy version of the Kidscreen-10 and parental quality of life using the EORTC QLQ C30 quality of life questionnaire. Additionally, the questionnaire comprised open questions about positive and negative changes parents perceived in their children as well as specific family- and child-related psychosocial needs. The majority of participants were mothers (91%), mainly diagnosed with breast cancer (59%). The participating parents provided data on 117 minor children. Parents mentioned positive changes in 40% of the children (e.g., being more attentive and helpful). Negative changes were reported in 35% of the children (e.g., being more anxious and clingy). Parents reported family-specific psychosocial supportive care needs for themselves as a parent (e.g., support regarding parenting concerns), support needs for the partner or the children. Moreover, parents expressed family-related information needs and needs regarding practical aspects (childcare, household help). Global quality of life was M=55.7 (SD 23.4) for parents and M=57.5 (SD=15.5) for children. Pearson’s correlation coefficient between parental and children’s quality of life was .377 (p<.001). To identify parents with cancer and children in need for additional support, health care providers should proactively inquire about the impact of the disease on the children. In terms of a comprehensive cancer care, the direct assessment of family impact and family-specific support needs in cancer patients with minor children allows for needs-based allocation to support offers.